Training habits in professional soccer players during COVID -19 confinement - Chena, M.; Gutiérrez-García, L.; Zapardiel, J. C.; Asín-Izquierdo, I. (Kinesiology, 2021)
The pandemic caused by COVID-19 has led to an unprecedented situation, forcing governments to take urgent measures and confine the population. These measures have also affected sports. Soccer competitions and training sessions were interrupted worldwide, causing the need to adapt training sessions to the new situation. The objective of this study is to observe and analyse training habits carried out during the COVID-19 confinement by Spanish professional soccer players of both sexes. An observational study was based on an ad-hoc telematic questionnaire during the COVID-19 state of alarm in Spain. The results showed that strength and conditioning training was of great importance in the training habits developed during the COVID-19 confinement, fundamentally that of strength and endurance capacities. Specificity was low as conditional capabilities were affected by contextual limitations. The findings of this study yielded very useful information related to the training habits of professional soccer players of both sexes and offered an unpublished reference database that could be used to address training planning at specific periods of the year (transition, vacations, emergencies, ...), with the aim of resuming competitive activity in the best conditions.